2021
DOI: 10.3390/cells10102539
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning to Decipher the Progression and Morphology of Axonal Degeneration

Abstract: Axonal degeneration (AxD) is a pathological hallmark of many neurodegenerative diseases. Deciphering the morphological patterns of AxD will help to understand the underlying mechanisms and develop effective therapies. Here, we evaluated the progression of AxD in cortical neurons using a novel microfluidic device together with a deep learning tool that we developed for the enhanced-throughput analysis of AxD on microscopic images. The trained convolutional neural network (CNN) sensitively and specifically segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“… Zille et al (2017) have verified that the hemin and hemoglobin-induced toxic mediators from lysed blood after ICH participate in the death of primary cortical neurons through ferroptosis and necroptosis, rather than caspase-dependent apoptosis or autophagy in vitro and in vivo . Moreover, Palumbo et al (2021) observed a time-dependent morphological degeneration of axons in hemin-induced primary cortical neurons, resulting in a declination of the axon area and enhancement of axonal swelling and fragment areas depending on a novel microfluidic device and a deep learning tool on microscopy. Hemorrhages in the internal capsule block the axonal transport to induce axonal dysfunction closely associated with an early decline of motor performance in mice with ICH ( Hijioka et al, 2016 ).…”
Section: Pathological Changes After Intracerebral Hemorrhagementioning
confidence: 98%
“… Zille et al (2017) have verified that the hemin and hemoglobin-induced toxic mediators from lysed blood after ICH participate in the death of primary cortical neurons through ferroptosis and necroptosis, rather than caspase-dependent apoptosis or autophagy in vitro and in vivo . Moreover, Palumbo et al (2021) observed a time-dependent morphological degeneration of axons in hemin-induced primary cortical neurons, resulting in a declination of the axon area and enhancement of axonal swelling and fragment areas depending on a novel microfluidic device and a deep learning tool on microscopy. Hemorrhages in the internal capsule block the axonal transport to induce axonal dysfunction closely associated with an early decline of motor performance in mice with ICH ( Hijioka et al, 2016 ).…”
Section: Pathological Changes After Intracerebral Hemorrhagementioning
confidence: 98%
“…During the course of the neurotoxicity assay, we noticed increased signs of axonal degeneration similar to those observed in tauopathies before cell death (Kneynsberg et al ., 2017). Blebs, also referred to in the literature as swellings, beadings, spheroids or varicosities, (Luo and O’Leary, 2005; Datar et al ., 2019; Yong et al ., 2019; Palumbo et al ., 2021) were observed at day 8 neuronal axons of H1/H1 haplotype, depleted for 5 weeks of AO, just before the neuronal cell death. These blebs started to develop at sub-regions of wells and propagated to other regions within 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Brain functions are mediated by multiple neuronal activities involving highly elaborate and complex synaptic connections. Neurons need to transport organelles, proteins, and lipids from the soma to the axon and dendrites and back again to maintain a normal functional state [ 49 , 50 ]. Microtubules act as conduits for both anterograde and retrograde transport of molecules [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%